„Odstąpcie, nie umarła dzieweczka, ale śpi” — life is a wait for death — from the homiletics of Fabian Birkowski - Poterała, Paulina (Starość i młodość w literaturze i kulturze, 2016)
The aim of this paper is to discuss the influence of the St Augustine thoughts on the sermon Go away, the girl is not dead, but asleep from The Sermons on Sundays Annual Celebrations. The article focuses on the issue of human dualism (division into soul and body) as well as life dualism (civitas Dei and civitas terrena).